2021
DOI: 10.1136/annrheumdis-2021-220865
|View full text |Cite
|
Sign up to set email alerts
|

Treating the skin with biologics in patients with psoriasis decreases the incidence of psoriatic arthritis

Abstract: ObjectivesTo compare the incidence of psoriatic arthritis (PsA) in patients with psoriasis (PsO) according to different treatments for their skin: topics/no treatment, conventional disease-modifying antirheumatic drugs (DMARDs) (cDMARDs) or biological DMARDs (bDMARDs).MethodsPatients with PsO without PsA followed at a university hospital were included in this retrospective cohort study. Patients were classified according to their treatment in topics (topics, phototherapy or no treatment), cDMARDs (methotrexate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…However, we are still unable to identify those patients with psoriasis who ultimately go on to develop PsA. It has been shown in observational studies that treatment of psoriasis might prevent the development of PsA 43 , 44 . Longitudinal research is needed to establish whether highly effective treatment of psoriasis can prevent or mitigate development of PsA.…”
Section: Research Agendamentioning
confidence: 99%
“…However, we are still unable to identify those patients with psoriasis who ultimately go on to develop PsA. It has been shown in observational studies that treatment of psoriasis might prevent the development of PsA 43 , 44 . Longitudinal research is needed to establish whether highly effective treatment of psoriasis can prevent or mitigate development of PsA.…”
Section: Research Agendamentioning
confidence: 99%
“…In three other studies, nail involvement “per se” did not emerge as a predictor of PsA occurrence but this finding was probably affected by the small sample size of the studies and by the lack of a reasonable time frame for observation. More recently, two retrospective cohort studies [ 37 , 38 ], not included in this SLR since they were published in July 2021, confirmed the original observation of Wilson et al supporting PsO nail involvement as predictor of PsA development. Among PsO nail lesions, only nail pitting was selected as a possible predictor [ 39 ].…”
Section: Discussionmentioning
(Expert classified)
“…Acosta Felquer et al [51] confirmed that the incidence of PsA in psoriatic patients treated with biologic drugs was significantly lower (incidence rate ratio (IRR) = 0.26; 95% CI 0.03 to 0.94; p = 0.0111) compared with patients treated with topical therapy, phototherapy, or no treatment. However, the authors also reported that PsA incidence under biolgics was not significantly lower compared with patients treated with conventional diseasemodifying antirheumatic drugs (methotrexate and cyclosporine) (IRR = 0.35; 95% CI 0.035 to 1.96; p = 0.1007).…”
Section: Discussionmentioning
confidence: 91%
“…Our study revealed that 8.5% (10 out of 118) psoriasis patients under biologics developed PsA during one-year follow-up, showing that new-onset PsA is possible for each existing class of biologics (anti-TNF, anti-IL12/23, anti-IL1, and anti-IL23), without any drug predilection and with the peripheral form representing most of the cases. Without any doubt, treating psoriasis with biologic drugs reduces the risk of PsA development [50,51].…”
Section: Discussionmentioning
confidence: 99%